The influence of school principals leadership and school culture on teacher performance - Sherly Sherly; Humiras Betty Marlina Sihombing; Efendi Efendi; Edy Dharma; Ayunda Evitasari (Institute of Computer Science (IOCS), 2023)
Teachers play a key role as the primary human resources in educational institutions, and they have a significant influence on the quality of education. High teacher performance directly contributes to the improvement of educational quality. Competent, dedicated, and continuously developing teachers can create a positive learning environment, motivate students, and achieve better academic achievements. The influence of school leadership and school culture on teacher performance is crucial. Through effective school leadership and a positive school culture, teacher performance can be enhanced, their motivation can be maintained, and student learning outcomes can be improved. This study aims to examine the significant influence of school leadership and school culture on teacher performance. The research population consists of 30 teachers from the Private High School Yayasan Perguruan Keluarga. Data collection is done through interviews, documentation, and questionnaire distribution. The data is processed using SPSS. The data is analyzed using quantitative descriptive analysis, including multiple linear regression analysis, simple linear regression analysis, correlation and determination coefficients, F-test, and t-test. The results of the study indicate that: (1) Teacher performance is positively and significantly influenced by school leadership and school culture, both simultaneously and partially, (2) there is moderately high correlation between school leadership, school culture, and teacher performance. The implication of this research indicates that school principals have a crucial role in creating an environment that facilitates good teacher performance. By considering the implications of this research, it is expected that schools can achieve an improvement in the quality of education through enhanced teacher performance.